Solusi Akad Murabahah bil Wakalah Pada Perbankan Syariah di Indonesia - Putra, Trisno Wardy; Rahman Ambo Masse; Nasrullah bin Sapa (MADINAH, 2024)
A country's economic development can grow if its business sector is doing well. To maintain the existence of business growth, a source of financing capital is needed. This research aims to critically examine the murabahah bil wakalah financing contract in Islamic banking and provide solutions to these problems. This research uses a qualitative method. This study is descriptive analytic in which data collection is carried out by reviewing the literature then analyzing and interpreting the content to produce conclusions and recommendations. The results of the study suggest that there are several problems that occur in the murabahah bil wakalah contract, including goods that are not fully owned by the bank, moral hazard in customers, and an explanation of the cost and profit. The solution is that banks are expected to form a special unit to purchase goods for customers, the need to emphasize the contract at the beginning of the transaction to prevent moral hazard, and the activeness of the sharia supervisory board in overseeing all transactions carried out at Islamic banks.